TENDENCIES OF INTERNATIONALIZATION OF HIGHER EDUCATION AS A FACTOR OF UNIVERSITY DEVELOPMENT - Zamkovaja, Alyona; Borysiuk, Iryna; Fizor, Natalia; Tsisak, Alona; Rokun, Daryna-Mariia; Molodan, Yuliia (Sworld-Us Conference proceedings, 2023)
The work considers the trend of internationalization of education, which is an important factor in the development of education and science, increases the competitiveness of universities not only in the country, but also in the world. It should be taken i